Growth in total factor productivity in the Ethiopian agriculture sector: Growth accounting and econometric assessments of sources of growth - Bachewe, Fantu Nisrane (International Food Policy Research Institute, 2012)
During the 2003/04–2008/09 period agricultural production in Ethiopia grew annually at 9.3 percent while cultivated area expanded at 4.7 percent. The remaining growth resulted from intensive use of other inputs, increased productivity, increased efficiency, or a combination of these factors. This study applies growth accounting and two econometric approaches on sector and administrative zone level data to investigate the issue.